Eine Ikonographie thermodynamischer Systemwirkungen für die Analyse von "Handlungen" - Krcal, Hans-Christian (AWI discussion paper series, 2025)
Thermodynamic laws are dominant and not deniable, we need to consider those in the context of system theory. From the system's perspective the entropy issue is decisive for the evaluation of future economic options and constraints. The paper sensitizes for entropic adequate firm acts in regard to resource management. Are system decisions reversible? The quality of entropy growth reflects the system's chance to keep up the space of acts, at least to prolong the space of acts. The system's observer and his information requirements are expressed in the entropy indicator. Graphic solutions, such as pictograms among others, are developed and highlighted which support the attempt to reduce or at least to lighten complexity in the management of resources. Graphical devices for the measurement of system entropy are presented. The combined illustrations in the paper enhance a firm's ability for operational resource management under the predominance of entropy law, for example within working groups.